Fundamentals of information systems - Stair, Ralph M (Thomson/Course Technology, 2008)
1. An introduction to information systems in organizations -- 2. Hardware and software -- 3. Organizing data and information -- 4. Telecommunications, the Internet, intranets, and extranets -- 5. Electronic commerce and transaction processing systems -- 6. Information and decision support systems -- 7. Specialized information systems: artificial intelligence, expert systems, virtual reality, and other systems -- 8. Systems development -- 9. Security, privacy, and ethical issues in information systems and the Internet.; Includes bibliographical references and index (p.437-451).